Fever management: Evidence vs current practice - El-Radhi, A Sahib Mehdi (Baishideng Publishing Group Co., Limited, 2012)
Fever is a very common complaint in children and is the single most common non-trauma-related reason for a visit to the emergency department. Parents are concerned about fever and it’s potential complications. The biological value of fever (i.e., whether it is beneficial or harmful) is disputed and it is being vigorously treated with the belief of preventing complications such as brain injury and febrile seizures. The practice of alternating antipyretics has become widespread at home and on paediatric wards without supporting scientific evidence. There is still a significant contrast between the current concept and practice, and the scientific evidence. Why is that the case in such a common complaint like fever The article will discuss the significant contrast between the current concepts and practice of fever management on one hand, and the scientific evidence against such concepts and practice.